2015
DOI: 10.3390/e17031387
|View full text |Cite
|
Sign up to set email alerts
|

Applied Cryptography Using Chaos Function for Fast Digital Logic-Based Systems in Ubiquitous Computing

Abstract: Abstract:Recently, chaotic dynamics-based data encryption techniques for wired and wireless networks have become a topic of active research in computer science and network security such as robotic systems, encryption, and communication. The main aim of deploying a chaos-based cryptosystem is to provide encryption with several advantages over traditional encryption algorithms such as high security, speed, and reasonable computational overheads and computational power requirements. These challenges have motivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 37 publications
(30 reference statements)
0
19
0
Order By: Relevance
“…It is a flag to break and break secure communication. ( Shukla ,Khare, Rizvi, Stalin& Kumar 2015,pp. 1387-1410).…”
Section: Definitionmentioning
confidence: 99%
“…It is a flag to break and break secure communication. ( Shukla ,Khare, Rizvi, Stalin& Kumar 2015,pp. 1387-1410).…”
Section: Definitionmentioning
confidence: 99%
“…Simulation results analyzed the efficiency and resistance against difference and linear cryptanalysis attacks and showed the high performance of the algorithm [5,29]. Fast encryption provides reliability and high security slightly, but at the same time highly reduces the running time [21,30,31]. Table 1 summarizes all the author's works on chaotic based encryption scheme on the basis of some characteristics.…”
Section: Featuresmentioning
confidence: 99%
“…It has been shown that a jerk equation, which is equivalent to a system of three first-order, ordinary, non-linear differential equations, is in a certain sense the minimal setting for solutions showing chaotic behavior. Therefore, chaos [1][2][3][4] has many applications in physics. With the exponential increase in information technology devices, the need for reliable authentication solutions has also been increased [5,6].…”
Section: Introductionmentioning
confidence: 99%